Circulating SERPINA3 improves prognostic stratification in patients with a de novo or worsened heart failure. (1st November 2021) - Delrue, Leen; Vanderheyden, Marc; Beles, Monika; Paolisso, Pasquale; Di Gioia, Giuseppe; Dierckx, Riet; Verstreken, Sofie; Goethals, Marc; Heggermont, Ward; Bartunek, Jozef
Abstract: Aims: We investigated the prognostic relevance of serpin peptidase inhibitor, clade A member 3 (SERPINA3) in patients admitted with a de novo or worsened heart failure (HF). Methods and results: In the first stage, 83 HF‐related left ventricular (LV) transcripts were examined in patients with congestive cardiomyopathy (CCMP, n  = 44) who died within 5 years and compared with age‐matched and haemodynamically matched CCMP survivors ( n  = 39) and controls with normal LV function ( n  = 17). Among 14 differentially expressed transcripts, myocardial gene and circulating SERPINA3 levels were up‐regulated in non‐survivors vs. survivors (2.40 ± 3.66 vs. 0.36 ± 0.22 units, P  < 0.01 and 334.7 ± 138.7 vs. 228.2 ± 83.1 μg/mL, P  < 0.01, respectively). While no significant transmyocardial gradient was detected, cytokine stimulation of human endothelial cells induced SERPINA3 secretion. In an independent validation cohort with a de novo or worsened HF ( n  = 387), circulating SERPINA3 levels > 316 μg/mL were associated with increased all‐cause mortality {hazard ratio [HR] [95% confidence interval (CI)]: 2.4 [1.5–3.9], P  = 0.0002} and its composite with unplanned cardiovascular readmission [HR (95% CI): 2.0 (1.2–3.3), P  = 0.004]. Patients with elevated SERPINA3 levels and elevated either N‐terminal pro brain natriuretic peptide or ST2 showed worse freedom from both endpoints. In a multivariate analysis, including established clinical risk factors, SERPINA3 remained independent predictor of all‐cause mortality together with age, gender, ST2, glomerular filtration, and pulmonary capillary wedge pressure. Conclusion: In patients with a de novo or worsened HF, increased SERPINA3 levels > 316 μg/mL are associated with increased mortality or unplanned cardiac readmission. Elevated SERPINA3 levels on top of established clinical predictors appear to identify a subgroup of HF patients at higher mortality risk. Prospective studies should further validate its value in prognostic stratification of HF.